Religious Revival among Orthodox and Pentecostals in Russia: Causes and Limitations1 - Löfstedt, Torsten (Religion, state & society, 2012)
In Russia in the late 1980s and early 1990s churches and denominations of all kinds grew quickly. Among those that grew most quickly were the Pentecostals. My impression is that by the mid-1990s, however, the growth rate for the leading Pentecostal denominations had slowed down considerably. In this paper I try to ascertain whether this in fact is the case and if so, what the causes for the slowdown in growth might have been. Because denominations have been reticent in sharing official membership statistics, I have looked for evidence of denominational growth rates in other places and have found evidence for a slowdown. I have then sought to explain the end of the revival among the Pentecostals. I find that the weakening of the Pentecostal churches is coupled with the strengthening of the Russian Orthodox Church in Russian society. The Orthodox Church has come to serve as an ethnic marker and it has successfully persuaded its adherents that non-Orthodox forms of Christianity are foreign sects. While I present little new empirical material, I ask new questions of the material available which help explain the slowdown in church growth among Russian Pentecostals.